Association Between Knowledge of Hypoglycemia and Likelihood of Experiencing Hypoglycemia Among Patients with Insulin-Treated Diabetes Mellitus - Almigbal TH (Diabetes, Metabolic Syndrome and Obesity, 2021)
Turky H Almigbal1– 3 1Department of Family and Community Medicine, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2King Saud University Medical City, King Saud University, Riyadh, Saudi Arabia; 3Vision College of Medicine, Vision Colleges in Riyadh, Riyadh, Saudi ArabiaCorrespondence: Turky H Almigbal Email almogbal@yahoo.comPurpose: This study aimed to evaluate the association between a patient’s knowledge about hypoglycemia and the likelihood of experiencing hypoglycemia.Participants and Methods: This cross-sectional study used a structured questionnaire to survey a representative sample of 429 adult males with insulin-treated diabetes mellitus (ITDM) in Saudi Arabia.Results: The main factors associated with increased risk of hypoglycemia included (a) a premixed insulin regimen, (b) a long duration of insulin treatment, (c) the use of oral hypoglycemic agents, and (d) a high hypoglycemia knowledge score. Insulin as a treatment modality directly affects the development of hypoglycemia among ITDM patients. Sweating is the most prevalent clinical manifestation among ITDM patients with hypoglycemia and could be an early indicator of hypoglycemia. Earlier detection of hypoglycemic signs may ultimately improve quality of life in ITDM patients.Conclusion: This research highlights the importance of healthcare providers educating ITDM patients about hypoglycemia. Furthermore, our results emphasize the urgent need to establish an educational program about hypoglycemia. ITDM patients are encouraged to learn more about hypoglycemia to help prevent future hypoglycemic attacks.Keywords: diabetes mellitus, insulin, hypoglycemia, hypoglycemia symptoms, patient education